Rula analysis of work-related musculoskeletal disorder among polypropylene fibrillated yarn industry worker using Digital Human Modelling (DHM) - Kabilmiharbi N.; Selamat F.E. (Malaysian Public Health Physicians Association, 2023)
Manual workers in plastics industry are often exposed to work related discomfort and pain while performing their daily task. These exposure leads to common occupational diseases such as Work-related Musculoskeletal Disorder (WMSD) or low back pain (LBP) which in turn will affect their working performance. The main objective for this study is to analyse the working posture of a manual worker that works in a polypropylene fibrillated yarn industry using RULA assessment in CATIA P3 V5R14 software. The subject were selected from the packaging area as the manual handling work are only present in that area. Based on the RULA analysis done by constructing the worker posture in the software, several awkward postures were identified to be high in risk factors. The postures that is high in risk is postures 3 which is due to lifting heavy loads and twisting or turning of the trunk. The postures obtained the final RULA analysis score of 7 and this indicates that changes must be done immediately. It is recommended that the company should increase the ergonomic awareness among the manual workers especially while performing their work and to redesign the working posture for the manual workers.